Identifying Milwaukee Youth in Critical Need of Intervention: Lessons from the Past, Measures for the Future (1991) - (:unkn) unknown (My University, 1991)
n 1990 Milwaukee County created a “Youth Initiative” to improve the delivery of services to youth. The Youth Initiative Committee made significant recommendations for altering the delivery of county social services and targeting "multiple-problem" families in Milwaukee zipcode areas 53204 and 53206. The Employment and Training Institute was asked to identify those families most in need of county social service intervention, to identify those children most at risk, and to provide measures of accountability which could be applied to government and private programs aimed at assisting these children and their families. Five target groups of youth are identified as possible priorities for county and school pilot interventions. The data review suggested that most children who arrive at Children's Court never escape from a cycle of poverty, abuse, neglect and subsequent delinquency. Most children appearing in court are also in the welfare system; most are on AFDC and many have been in county social service systems. Two-thirds of boys who appear at Children's Court for the first time as Children in need of Protective Services (CHIPS cases) returned as delinquents after they reach age twelve. For boys appearing at Children's Court for the first time as delinquents, almost half returned at least once more as delinquents. For those assigned to care ordered by the court, the picture was even bleaker. Three-fourths of boys assigned to group homes or residential treatment centers returned one or more times as delinquents, and over half of boys assigned to probation return again.
Keywords: criminal justice; child abuse; child poverty; social services